[123I]β-CIT SPECT imaging of dopamine and serotonin transporters in Parkinson’s disease and multiple system atrophy - Berding, G.; Brücke, Th.; Odin, P.; Brooks, D. J.; Kolbe, H.; Gielow, P.; Harke, H.; Knoop, B. O.; Dengler, R.; Knapp, W. H. (Nuklearmedizin - NuclearMedicine, 2003)
Aims: Definition of the regional pattern of dopamine transporter (DAT) dysfunction in advanced Parkinson’s disease (PD) and evaluation of a potential correlation between DAT binding and symptoms; elucidation of the role of DAT imaging in the differential diagnosis of PD and multiple system atrophy (MSA); assessment and comparison of serotonin transporter (SERT) binding in PD and MSA. Methods: [123I]ß-CIT SPECT was performed in 14 patients with advanced PD, 10 with moderate MSA and 20 healthy persons. Specific to nonspecific tracer binding ratios (V3’’) were calculated via ROI analysis of uptake images at 4 h (SERT binding) and 24 h (DAT binding) p. i. Results: In PD bilateral reduction of striatal DAT binding (63-70%) was seen. The caudate ipsilateral to the clinically predominantly affected side showed relatively the least impairment. Significant correlations (r = -0.54 to -0.64) between DAT binding and Hoehn and Yahr stage, UPDRS-scores and duration of disease were found. In MSA DAT binding was less reduced (40-48%) targeting the putamen contralateral to the side of clinical predominance. Significantly lower SERT binding was observed in PD midbrain and MSA hypothalamus compared to controls – and in MSA relative to PD mesial frontal cortex. Conclusions: In advanced PD striatal DAT binding is markedly reduced with the least reduction in caudate ipsilateral to the clinically predominantly affected side. In moderate MSA with asymmetrical symptoms DAT dysfunction is predominant in the contralateral putamen, a pattern seen in early PD. The reduction of SERT in the midbrain area of PD patients suggests additional tegmental degeneration while in MSA the serotonergic system seems to be more generally affected.
Keywords: Dopamine transporter; serotonin transporter; Parkinson’s disease; multiple system atrophy; SPECT; beta-CIT